PENINGKATAN MANAJEMEN USAHA DAN PRODUKTIVITAS UKM BATIK DI KABUPATEN MALANG ( Studi Kasus Pada UKM Batik ‘B-Dhan’ Kab.Malang) - Dwi Danesty Deccasari; Marli Marli; Zainul arifin; Rina Rahmawati (Jurnal Pengabdian kepada Masyarakat, 2020)
Batik is a work of art belonging to Indonesia that cannot be denied. It is proven that in almost all corners of the archipelago, from the western tip of Sumatra to the eastern tip of Papua, you can easily find traditional batik centers. It is very appropriate that UNESCO has recognized that batik is the original cultural heritage of Indonesia. The tighter competition in batik business required new business breakthroughs both in terms of marketing methods and in terms of productivity. This needs to be done at “B-Dhan” Batik UKM which is located in Sumberbening Village, Bantur District, Malang Regency because the batik business is one of the livelihoods for the surrounding community, which in fact has a lot of seasonal unemployment and realizes the strength of the village economy. The problems faced by SMEs mentioned above are the limited ownership of batik production equipment available and from a management perspective, the ability to record, marketing and business management knowledge is still very low, and this will have an impact on the preparation of business strategies that must be carried out amid increasingly competition. high. The solution is to provide batik production equipment, increase accounting skills for SMEs, mastery of marketing management, and increase batik skills by providing trainings. The implementation of community service programs by considering the potential of batik SMEs in rural areas is expected to create equitable distribution of community welfare.